Mitigation measures of greenhouse gases adopted in the farming sector: economic assessment and impact in Mexico - Elizondo Cordero, Alejandra; Ibarrarán Viniegra, María Eugenia; Boyd, Roy Gene (Agricultura, Sociedad y Desarrollo, 2020)
The objective of this study is to analyze the economic impact of actions in the farming sector to mitigate emissions of greenhouse gases and, therefore, to contribute to the climate policy in the country. For this purpose, a series of simulations of these policies are made with a computable general static equilibrium model to determine their effect in production, consumption and welfare of different population groups according to their income. The research hypothesis is that the agricultural policies chosen, which are being implemented today, can simultaneously drive economic growth and contribute to the country’s climate policy. The results show that there is an alignment of objectives between the different ministries and programs, and that the policy actions suggested contribute to economic growth, although in a limited way. There is a potential increase in the value of agricultural production of 6.8%, with an increase in the consumption of foods of almost 1%. In addition, land rental and salaries increase their value as a result of primary sector policies. The results obtained are in line with those from other studies cited in the manuscript.